Quantitative characterization of interface delamination in composite T-joint using couplant-free Lamb wave methods - Padiyar M, Janardhan; Balasubramaniam, Krishnan (Sage, 2015)
Research in quick Non-Destructive Evaluation methods for field maintenance of aircraft has become a focus of attention due to increase in the use of co-cured skin-stiffened composite structures. When Lamb wave propagates over skin-stiffened structure, the occurrence of multiple modes is unavoidable due to structural features such as stringers and stiffeners, which in turn makes the interpretation of the received wave difficult and limits the defect-detection ability of Lamb waves. Using Finite Element simulations, the propagation of incident S0 Lamb mode in a typical composite T-joint with delamination between the flange and skin (interface) is investigated. Arrival time delays of the out-of-plane mode-converted wave packets are found to be promising indicator for quantitative detection and sizing of the delamination. A novel experimental technique of combining a liquid couplant-free transduction scheme using dry-coupled roller transducer (contact probe) for generating S0 mode and an air-coupled transducer (non-contact probe) as a receiver is proposed. This transduction scheme helps in selectively separating mode-converted wave packets. This investigation also establishes quantitative B-scan imaging method for characterization of delamination in the T-joint. Experimental results show a good agreement with Finite Element predictions.
Keywords: wave propagation; air-coupled ultrasonics; S0 mode; delamination; Composite structure